2016
DOI: 10.1371/journal.pbio.1002537
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Tumors Originate in Tumor Hotspots, a Tissue-Intrinsic Microenvironment

Abstract: Malignant tumors are caused by uncontrolled proliferation of transformed mutant cells that have lost the ability to maintain tissue integrity. Although a number of causative genetic backgrounds for tumor development have been discovered, the initial steps mutant cells take to escape tissue integrity and trigger tumorigenesis remain elusive. Here, we show through analysis of conserved neoplastic tumor-suppressor genes (nTSGs) in Drosophila wing imaginal disc epithelia that tumor initiation depends on tissue-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 54 publications
10
107
0
Order By: Relevance
“…While scrib basal extrusion is tumor suppressive, hyperactivating scrib cell extrusion drove aberrant apical extrusion and lethal, luminal tumors (Figure 4c) (Vaughen and Igaki, 2016), underscoring that balanced extrusion rates are critical for homeostasis. This strongly parallels recent findings from scrib-RNAi experiments in wing discs, where scrib KD cells selectively overgrow when extruded apically at tumor “hotspots” characterized by dense, basal extracellular matrix (Tamori et al, 2016). Thus, luminal scrib tumors can avoid engulfment by neighboring cells (Ohsawa et al, 2011) or circulating hemocytes (Pastor-Pareja et al, 2008) while simultaneously capitalizing on endogenous JAK/STAT signaling at hotspots (Tamori et al, 2016).…”
Section: Cell Competition and The Active Extrusion Of Aberrant Cellssupporting
confidence: 86%
“…While scrib basal extrusion is tumor suppressive, hyperactivating scrib cell extrusion drove aberrant apical extrusion and lethal, luminal tumors (Figure 4c) (Vaughen and Igaki, 2016), underscoring that balanced extrusion rates are critical for homeostasis. This strongly parallels recent findings from scrib-RNAi experiments in wing discs, where scrib KD cells selectively overgrow when extruded apically at tumor “hotspots” characterized by dense, basal extracellular matrix (Tamori et al, 2016). Thus, luminal scrib tumors can avoid engulfment by neighboring cells (Ohsawa et al, 2011) or circulating hemocytes (Pastor-Pareja et al, 2008) while simultaneously capitalizing on endogenous JAK/STAT signaling at hotspots (Tamori et al, 2016).…”
Section: Cell Competition and The Active Extrusion Of Aberrant Cellssupporting
confidence: 86%
“…Cell extrusion and cell competition are intimately linked to tissue homeostasis and tumor progression (Gu and Rosenblatt, 2012; Ballesteros-Arias et al, 2013; Enomoto et al, 2015), and the direction of cell extrusion can dictate whether a cancer is initiated or suppressed (Hogan et al, 2009; Slattum and Rosenblatt, 2014; Tamori et al, 2016). We also found that modulating extrusive signaling either promoted or suppressed scrib tumorigenesis (Figure 7): while plain Robo2 or Ena hyperactivation triggered basal epithelial cell extrusion followed by cell death (Figures 5B, 5C, and S4S–S4Tʹ), Robo2-Ena activation in scrib mutant cells unexpectedly accelerated both basal and apical extrusion into the lumen (Figures 4G–4L).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the aberrant polarity of scrib cells permits a tumor-suppressive, basal cell-extrusion mechanism to deleteriously promote randomized cell extrusion and luminal tumorigenesis. Indeed, luminal extrusion was recently identified as a causal mechanism of scrib tumorigenesis in the Drosophila wing disc (Tamori et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…This ‘tumor-suppressive competition’ is partially independent of caspase-dependent apoptosis [36,37]. Although apoptosis does contribute, mutant cells are also removed by extrusion from mosaic epithelia, in both apical and basal directions [38**,39**]. …”
Section: Tumor-suppressive Competitionmentioning
confidence: 99%
“…Here cells delaminate apically and can grow as neoplastic tumors by exploiting apical Jak-Stat signaling [38**]. …”
Section: Tumor-suppressive Competitionmentioning
confidence: 99%